Awareness and Adoption of Evidence-Based Instructional Practices by STEM Faculty in the UAE and USA - Melinda Joy Biggs Albuquerque; Dina Mustafa Mohammad Awadalla; Francisco Daniel Benicio de Albuquerque; Ashraf Aly Hassan (MDPI AG, 2023)
There has been a widespread call for improvement in undergraduate STEM education, leading to what are known as evidence-based instructional practices (EBIPs). However, EBIP usage in STEM is a more recent phenomenon in the United Arab Emirates, which is historically known for its passive teaching practices but is now taking strides to transform its educational system. This study sought to assess (i) STEM faculty EBIP awareness, adoption, and ease-of-implementation perceptions from STEM faculty at a leading university in the United Arab Emirates and the demographic factors correlated with faculty responses, and (ii) the contextual factors that influence faculty EBIP adoption. Data was compared to that of STEM faculty at a top-tier research and teaching university in the United States of America. Finally, this study sought to provide a snapshot of current STEM faculty teaching practices when both a leader (United States of America) and a newcomer (United Arab Emirates) in STEM EBIPs were considered. A survey containing 16 teaching practices-3 traditional, 13 EBIPs-along with 20 contextual factors was developed and completed by faculty. EBIP awareness and usage were positively affected by time spent on teaching, teaching experience, and teaching workshop participation, and negatively affected by more class time spent lecturing. Significant contextual factors point to potential factors for consideration in efforts to improve EBIP adoption.